Rekonstruksi Sejarah Kebangkitan Nasional (Jurnal Adabiya, 2020)
The journey of Indonesia history is facing a lot of critics form many elements of nation, including the decision of first president of Indonesia Ir. Soekarno to acknowledge the establishment of organization of Budi Utomo as a national resurgence day in 1948, this article try to look back at the historical facts, because there are other organizations already exist before Budi Utomo, by providing historical facts that are not being awared of until today, in a hope to clarifiy that Budi Utomo is not the starting point of Indonesian resurgence.
Keywords: history; resurgence; national